Uji Aktivitas Antiinflamasi Nanopartikel Ekstrak Etanol Rimpang Temulawak (Curcuma xanthorrhiza Roxb.) dengan Metode Penghambatan Denaturasi Protein - Yunahara Farida; Deni Rahmat; Agi Widia Amanda (Fakultas Farmasi Universitas Pancasila, 2018)
Javanese turmeric rhizome (Curcuma xanthorrhiza Roxb.) has been known to have many health benefits as antibacterial, anti-inflammatory, antidiabetic and anticancer. The purpose of this study was to compare the anti-inflammatory activity of temulawak rhizome extract with its nanoparticles. Temulawak rhizome extract was obatained by maceration using 96% (v/v) ethanol as a solvent. The extracts were made into nanoparticles by ionic gelation method which used chitosan and tripolyphosphate. The results of antiinflammatory activity test using a method of inhibiting protein denaturation showed the persentage of inhibition of protein denaturation (IC50) of the extract of temulawak rhizome of 521.67±5.80 ppm while the IC50 of the nanoparticles was 398.02±1.78 ppm. Accordingly, the antiinflammatory activity of the nanoparticles was better than the extract of temulawak rhizome.